Assessing impacts of groundwater on geothermal heat exchangers: A review of methodology and modeling. (May 2022) - Zhao, Zilong; Lin, Yu-Feng; Stumpf, Andrew; Wang, Xinlei
Abstract: Despite the intensive studies and advances have been made, the penetration of geothermal heat exchangers (GHEs) and ground coupled heat pump (GCHP) systems has been constrained due to high-upfront capital cost. On the other hand, the recent research has revealed the enormous influence that complex geologic and hydraulic systems have on the GCHP efficiency, especially the impact of groundwater. Without this knowledge, their design and operation may lead to lower economic competitiveness or potential systematic degradation. This paper reviews the challenges of integrating groundwater impacts on the performance of GHEs and the strategies through industry standard models. Three principal methodologies consisting of analytical, numerical, and experimental approaches are identified. Multiple topics that have received much debate, such as soil freezing and thawing, are addressed with their latest developments. Furthermore, the environmental impacts associated with GHEs' thermal response that consider groundwater flow are discussed. It is found that in most situations the presence of flowing groundwater enhances the GHE performance, although potential adverse effects exist when the operation is not monitored and mitigated. However, the natural uncertainties in the geology and the advanced hybrid GCHP implementations needs further exploration to facilitate the on-going groundwater-associated research including borehole thermal storage. Highlights: Reviewed geothermal heat exchanger (GHE) models under the groundwater impacts. Models were categorized and analyzed based on their methods and solved challenges. GHE performance improvements induced by groundwater were quantitively summarized. Environmental concerns associated with groundwater were identified. A guidance for further research on GHEs considering groundwater was proposed.